The Medium is the Archive - Enrico Terrone (Law Text Culture, 2018)
There has been much discussion about how digital technologies have changed the media. In this paper I will propose a reflection on how digital technologies can also deeply modify our conception of the media. In particular, I will show how digital technologies challenge a number of conceptual distinctions that underlie, almost as dogmas, most current discussions on media. I will analyse and criticise the following dogmatic distinctions: communication / recording; medium / archive; vehicle / store; act / object; content / form.